PENDAMPINGAN MANAJEMEN SDM BAGI SISWA SEKOLAH UNTUK MEMBENTUK KEPERCAYAAN DIRI DALAM MENGHADAPI PERSAINGAN GLOBAL DI DESA BANTARAGUNG, MAJALENGKA, JAWA BARAT - Yayah Sutisnawati; Hadi Purnomo; Lita Wulantika; Annisa Mayasari; Muhammad Fajri Ramadhan (POLITEKNIK LP3I JAKARTA, 2026)
This community service program aims to enhance leadership capacity and develop students’ self-confidence amid the challenges of globalization and technological advancement, which require the younger generation to possess high-quality human resources, both academically and non-academically. One important aspect that students need to develop is self-confidence as preparation for facing global competition. However, many students in Bantaragung Village still face limitations in self-development, communication skills, and the courage to express their opinions. Therefore, this community service activity seeks to provide human resource management mentoring for school students in order to improve their self-confidence and interpersonal skills. The implementation methods of this program included counseling sessions, training, interactive discussions, and direct mentoring for students. The materials delivered covered the introduction to human resource management, public speaking, soft skills development, learning motivation, leadership, as well as emotional management and positive mental attitudes. This activity involved school students as the main participants through a participatory approach, encouraging them to be more active in the learning process. The results of the program indicate that human resource management mentoring had a positive impact on increasing students’ self-confidence. Students became more courageous in communicating, more active in discussions, and more motivated to develop their personal potential. In addition, this activity helped students understand the importance of self-quality development as preparation for facing the challenges of globalization and future competition. Therefore, the human resource management mentoring program for school students in Bantaragung Village can serve as a strategic effort to shape a confident, independent, and globally competitive younger generation.